Exploring the protective role of caffeine against Taraxacum-Induced ribotoxic stress mediated through autophagy and mitochondrial depolarization - Chien-Jung Lin; Shu-Ting Liu; Zih-Syuan Wu; Shih-Ming Huang; Teng-Wei Chen (Scientific Reports)
Abstract The ribotoxic stress response is a pathway that gets activated when ribosomes get impaired, leading to disruptions in protein synthesis, increased inflammatory signaling, and cell death if left unresolved. Taraxacum can induce apoptosis-associated ribosomal RNA (rRNA) cleavage, however, the exact working mechanism of Taraxacum-induced rRNA cleavage remains unclear. In this study, we used the RNA integrity (RIN) value and 28S/18S ratio to confirm the integrity of experiments. Our RNA sequencing data showed that Taraxacum formosanum (T. formosanum) upregulated 893 genes and downregulated 509 genes and triggered hallmark genes of spliceosomes, TNF-α signaling via NF-κB, inflammatory response, and IL6-JAK-STAT3 signaling. Additionally, T. formosanum imbalanced the levels of ribosomal proteins of the large and small subunits. We found that caffeine was the only screening agent that could rescue the cleavage of 28S and 18S rRNA induced by T. formosanum. However, caffeine failed to rescue T. formosanum-targeted mRNAs when the RIN values were relatively lower. T. formosanum induced the N-terminal clipping of histone H3, which was observed not only in human HeLa cervical cancer cells but also in human Huh6 and HepG2 liver cancer cells. Our study revealed that caffeine could reverse the effects of T. formosanum on the reduction of autophagy and the disruption of mitochondrial membrane potential. However, caffeine could only change the populations of necrotic and apoptotic cells but not T. formosanum-induced cell death. By providing detailed information on Taraxacum-induced rRNA cleavage and N-truncated histone H3’s mechanisms of gene regulation, we hope to understand their respective cellular death and survival stresses.